The Experience with Macro-Prudential Policies of the Central Bank of the Republic of Turkey in Response to the Global Financial Crisis - Kenc, Turalay; Turhan, M. Ibrahim; Yildirim, Onur (2012)
This brief country case study on Turkey aims to summarize the fundamental developments in the banking sector, which represents almost 90 percent of the financial sector in the country. The brief has two parts. The first covers the 2001 financial crisis and the developments until end of 2007, the year before the global financial crisis of 2008 started. The second part focuses on the macro-prudential policies applied by the Central Bank of the Republic of Turkey in response to the global financial crisis in three phases: (i) full liquidity support after Lehman Brothers' collapse (September 2008), (ii) the exit strategy (April 2010), and (iii) the new policy mix (final quarter of 2010).